Washington View: Academic emphasis may not be enough for Americans. (September 2016) - Ferguson, Maria
The results of the 48th annual PDK Poll of the Public's Attitudes Toward the Public Schools suggest that Americans may have tired of the relentless focus on academics that occurred during the No Child Left Behind era and that they want more emphasis on preparing students for life after school.